Paul Hammond interviewed by Mark Gordon in the Esso Performing Arts collection - Hammond, Paul, 1922-2010.; Potter, Michelle, 1944-; Gordon, Mark V., 1956-; National Library of Australia; Esso Australia; Esso Performing Arts and Oral History Archive Project (1989)
Hammond speaks of his childhood and education; interest in de Basils touring Russian ballets; dance lessons from Helene Kirsova and Mischa Burlahov whilst at school and later when working as a bank clerk; experiences dancing with the newly formed Kirsova ballet; Kirsova's technique and philosophies; ballet in Australia in the 1930s and 1940s; experiences with Borovansky Ballet Company and J.C. Williamson organization; Borovansky's ideas on dance; working with Sir Robert Helpmann in the film the Red Shoes; experiences with the Metropolitan Ballet in England and the Brussels Opera; returning to Australia and rejoining Borovansky Ballet; the founding of the Australian Ballet; and his work as a choreographer, teacher and archivist.
Transcript includes photographs.
Part of a collection of oral history interviews produced by the Esso Performing Arts and Oral History Archive Project.
Recorded in South Melbourne, Victoria, on February 21 and 22.
Digital master available
Transcript (typescript, 148 p.)
Keywords: Hammond, Paul, -- 1922-2010 -- Interviews; Kirsova Australian Ballet -- History; Australian Ballet -- History; Ballet dancers -- Australia -- Biography; Ballet dancers -- Australia -- Interviews